Eye Diseases Direct Interest to Complement Pathway and Macrophages as Regulators of Inflammation in COVID-19. Issue 1 (January 2021) - Jager, Martine J.; Seddon, Johanna M.
Abstract : Abstract: Many of the risk factors for developing severe coronavirus disease 2019 (COVID-19) are also risk factors for eye diseases such as age-related macular degeneration (AMD). During the past decades, macrophages and the complement pathway (as a part of the innate immune system) have been identified as important contributors to the development of AMD, and we suggest that these mechanisms are of similar importance for the clinical course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Based on the experience with AMD, we discuss how behavioral factors such as diet, smoking and higher body mass index, as well as genetic determinants such as the complement and immune pathway genes may lead to the overactive inflammatory phenotypes seen in some patients with COVID-19, and may in part explain the heterogeneity of disease manifestations and outcomes. Based on this experience, we discuss potential genetic research projects and elaborate on preventive and treatment approaches related to COVID-19.